A single 36-h water-only fast vastly remodels the plasma lipidome - Hong, Brian V.; Rhodes, Christopher H.; Agus, Joanne K.; Tang, Xinyu; Zhu, Chenghao; Zheng, Jack Jingyuan; Zivkovic, Angela M. (Frontiers in Cardiovascular Medicine, 2023)
Background: Prolonged fasting, characterized by restricting caloric intake for 24 hours or more, has garnered attention as a nutritional approach to improve lifespan and support healthy aging. Previous research from our group showed that a single bout of 36-hour water-only fasting in humans resulted in a distinct metabolomic signature in plasma and increased levels of bioactive metabolites, which improved macrophage function and lifespan in C. elegans. Objective: This secondary outcome analysis aimed to investigate changes in the plasma lipidome associated with prolonged fasting and explore any potential links with markers of cardiometabolic health and aging. Method: We conducted a controlled pilot study with 20 male and female participants (mean age, 27.5 ± 4.35 years; mean BMI, 24.1 ± 2.66 kg/m2) in four metabolic states: 1) overnight fasted (baseline), 2) 2-hour postprandial fed state (fed), 3) 36-hour fasted state (fasted), and 4) 2-hour postprandial refed state 12 hours after the 36-hour fast (refed). Plasma lipidomic profiles were analyzed using liquid chromatography and electrospray ionization mass spectrometry. Results: Several lipid classes, including lysophosphatidylcholine (LPC), lysophosphatidylethanolamine (LPE), phosphatidylethanolamine, and triacylglycerol were significantly reduced in the 36-hour fasted state, while free fatty acids, ceramides, and sphingomyelin were significantly increased compared to overnight fast and fed states (P < 0.05). After correction for multiple testing, 245 out of 832 lipid species were significantly altered in the fasted state compared to baseline (P < 0.05). Random forest models revealed that several lipid species, such as LPE(18:1), LPC(18:2), and FFA(20:1) were important features in discriminating the fasted state from both the overnight fasted and postprandial state. Conclusion: Our findings indicate that prolonged fasting vastly remodels the plasma lipidome and markedly alters the concentrations of several lipid species, which may be sensitive biomarkers of prolonged fasting. These changes in lipid metabolism during prolonged fasting have important implications for the management of cardiometabolic health and healthy aging, and warrant further exploration and validation in larger cohorts and different population groups.